Non-fabricated ocular prosthesis posteviseration: Prostesis mata non-fabrikasi pascaeviserasi - Aksani Taqwim; Rezki Wahyuni; Edy Machmud (Makassar Dental Journal, 2023)
Eyeball loss is a traumatic process as it can cause functional, media, psychological and aesthetic problems. Patients who re-quire treatment with specialised eye prostheses are those who have lost ocular structures through removal of orbital contents or orbital enucleation to accelerate physical and psychological healing and improve aesthetics. This article reports the fabrication of an eye prosthesis as a rehabilitative treatment in a patient who had undergone orbital enucleation. A 38-year-old man came to RSGMP Universitas Hasanuddin Makassar referred by an ophthalmologist with complaints of left eyeball loss due to trauma. The patient wanted to have a prosthetic eye made immediately to restore his appearance and self-confidence. Examination of the eye socket showed a healthy conjunctiva and no infection. The treatment was the fabrication of a non-fabricated eye pros-thesis made from acrylic resin. The fabricated non-fabricated eye prosthesis had advantages in terms of retention, stability, aes-thetics and patient comfort. It was concluded that the ocular prosthesis can reduce the psychological trauma caused by the loss of the eyeball, thus increasing the patient's confidence in social life.